(untitled) (Web of Teachers: Inderscience Research, 2024)
The article discusses the use of storytelling as an innovative method of teaching Russian as a foreign language (RFL). We will explore the key aspects of this methodology, including visual aids, familiar storylines, and approaches to passive listening, which contribute to more effective acquisition of language skills and cultural contexts. The article highlights that the use of storytelling not only improves linguistic competencies but also establishes an emotional connection with the learning material, boosting students’ motivation and making the learning process both engaging and meaningful.